The Effect Of Capital Structure, Financial Performance, And Capital Intensity On Company Stock Prices - Kristina Timu Welan (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study aims to analyze the influence of capital structure, financial performance, and capital intensity on stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019–2024 period. The study uses a quantitative approach with secondary data in the form of annual financial reports. The sample was determined through purposive sampling of 52 companies with a total of 312 observations. The analysis was conducted using panel data regression with the Fixed Effect Model (FEM). The results show that partially, capital structure and capital intensity have no significant effect on stock prices, while financial performance has a significant effect. Simultaneously, all three variables have a significant effect on stock prices. This finding indicates that investors consider financial performance, especially profitability, more heavily in making investment decisions.